Post-Growth Geographies Spatial Relations of Diverse and Alternative Economies - Lange, Bastian; Hülz, Martina; Schmid, Benedikt; Schulz, Christian (transcript Verlag, 2021)
Post-Growth Geographies examines the spatial relations of diverse and alternative economies between growth-oriented institutions and multiple socio-ecological crises. The book brings together conceptual and empirical contributions from geography and its neighbouring disciplines and offers different perspectives on the possibilities, demands and critiques of post-growth transformation. Through case studies and interviews, the contributions combine voices from activism, civil society, planning and politics with current theoretical debates on socio-ecological transformation
Online resource; title from title screen (viewed February 28, 2022)
Keywords: Degrowth; Post-growth; Transformation; Post-growth Economy; Post-growth Planning; Sustainability Transition; Sufficiency; Economy; Space; City; Social Geography; Urban Planning; Economic Sociology; Geography; Wirtschaftsgeografie; Raumordnung; Postwachstumsökonomie; Wirtschaftssoziologie; Sozialraum; Aufsatzsammlung